Emerging Role of Helicobacter pylori in the Immune Evasion Mechanism of Gastric Cancer: An Insight Into Tumor Microenvironment-Pathogen Interaction - Li, Zhifang; Zhang, Wenqing; Bai, Jinyang; Li, Jing; Li, Hong (Frontiers in Oncology, 2022)
Helicobacter pylori (H. pylori) infection is the strongest causative factor of gastric cancer. Growing evidence suggests that the complex crosstalk of H. pylori and the tumor microenvironment (TME) exerts a profound influence on gastric cancer progression. Hence, there is emerging interest to in-depth comprehension of the mechanisms of interplay between H. pylori and the TME. This review discusses the regulatory mechanisms underlying the crosstalk between H. pylori infection and immune and stromal cells, including tumor-associated macrophages (TAMs), neutrophils, dendritic cells, myeloid-derived suppressor cells (MDSCs), natural killer (NK) cells, B and T cells, cancer associated fibroblasts (CAFs), and mesenchymal stem cells (MSCs), within the TME. Such knowledge will deepen the understanding about the roles of H. pylori in the immune evasion mechanism in gastric cancer and contribute to the development of more effective treatment regimens against H. pylori-induced gastric cancer.